A Modified Preparation Method of Ideal Platelet-Rich Fibrin Matrix From Whole Blood - Reksodiputro, Mirta Hediyati; Harahap, Alida Roswita; Setiawan, Lyana; Yosia, Mikhael (Frontiers in Medicine, 2021)
One bioproduct that is widely used in the wound healing process is Platelet Rich Plasma (PRP). PRP is a liquid solution with high autologous platelet concentration, making it a good source of growth factors to accelerate wound healing. Recent development in PRP had created a new product called Platelet Rich Fibrin Matrix (PRFM), which has a denser and more flexible structure. PRFM is the newest generation of platelet concentrate with a fibrin matrix that holds platelet in it. The key concept in creating PRFM from PRP is the addition of CaCl2 followed by centrifugation, which converts fibrinogen to fibrin, and the fibrin cross-links to form a matrix that contains viable platelets. There are many commercially available kits to create PRFM, but they are often expensive and uneconomical. This research will test a modified method of making ideal PRFM from PRP without any commercial kits. The modified method will include determining the minimum level of CaCl2 used, the type of centrifuge, and the speed and duration of centrifugation. By performing a modified preparation method on five samples of whole blood, it was found that the ideal PRFM could be made by mixing PRP with 25 mM CaCl2 and centrifuging it at a speed of 2264 G for 25 minutes at room temperature. The PRP and PRFM platelet counts of this method tend to be lower than the platelet counts found in other studies. Although visually comparable, further study is needed to compare the performance of PRFMs made with this method and PRFMs made with commercial kits.